Logistic Management in Pandemic: An Empirical Study of Iron and Steel Sector in India - Ray, Dr. Manidatta; Mishra, Dr. Satyakama (The journal of contemporary issues in business and government, 2022)
Since 2019, Covid -19 pandemic has changed our style of living, our businesses. Most of the countries in the world are facing problems to main their economy during this pandemics period. When government of India was announced first phase of lock down, every business operation were paused and no one have an idea to run it during this situations. After relaxation of lock down businesses started with new and innovative matter. This paper focused on supply chain business and their management during the pandemic period by taken into condensation of their association with iron and steel sector in India. For this paper, empirical study of performance selected iron and steel companies have been done on the basis of their logistic management. Data of SAIL, TATA STEEL, JSW are taken into account for analysis purpose. The result of the study is expected to help for the companies for future development.